Instagram Captions by Berlian College Students: A Blend of Indonesian and English Code-Mixing - Lalu Isnaeni Rahman; Dedy Ahsan Muttaqin (Yayasan Insan Mulia Bima, 2024)
This study delves into the vibrant phenomenon of code-mixing in Instagram captions created by students, exploring how they seamlessly blend Indonesian and English. This research provides fresh insights into bilingual expression in a digital context by focusing on the specific types of code-mixing used and the underlying factors driving its adoption. Using a descriptive qualitative approach, the study analyzed Instagram posts from Berlian Education Training College students aged 18 to 25, focusing on 11 participants with higher English proficiency. The data collection technique used in this study is the documentation technique. The researcher documented natural data obtained from utterances posted on Instagram. The findings reveal a distinct insertion pattern: English words are strategically placed at Indonesian sentences' beginning, middle, or end. Factors influencing this linguistic blend include bilingualism, social background, vocabulary range, context, and interaction dynamics. This research sheds light on how young bilingual speakers creatively navigate their linguistic repertoire to communicate and connect on social media.